Antecedents and consequences of price promotions effectiveness - Isabel María Rosa Díaz (Cuadernos de Gestión, 2012)
From an approach of market orientation, the present research analyzes the influence of several factors on the efficiency of price promotions. The above mentioned factors are related to purchase behavior (the importance of price in the decision process and the consumers level of price knowledge), as well as to the sociocultural and demographic characteristics (gender, education level, and income level). The empirical study developed, based on a sample of 600 consumers, has allowed to draw a common profile for consumers who are attracted to price promotions sales.